Africa and Portugal - Carvalho, C. (Africa and the world: Bilateral and multilateral international diplomacy, 2018)
Discusses Portugal’s foreign policy, which is exclusively directed towards the Portuguese-speaking African countries-Países Africanos de Língua Oficial Portuguesa (PALOP)-marked by aid and cooperation; trade and economic exchanges; and political and strategic mediation. The author underscores that Portugal’s relationship with Lusophone Africa has been greatly determined by its accession to the European Union (EU) in 1986, and the end of civil war in Angola and Mozambique. The chapter critically assesses the role of the Community of Portuguese-Language Countries as an effective forum for implementing economic and development policies in Africa during the post-Cold War era. But given the mixed interests of Portugal, in Angola, Mozambique, and other PALOP countries, the author notes that Portugal’s influence in Africa was largely eclipsed by Brazilian interests, especially during the administration of Luiz Inácio “Lula” da Silva.